Peran Kepemimpinan Pendidikan Islam dalam Meningkatkan Kualitas Kedisiplinan dan Kemandirian Gen-Z di Sekolah - Agung Panji Utomo; Husnul Buairi; Yudin Citriadin; Muhammad Thohri; Syatriadin Syatriadin (Universitas Muhammadiyah Mataram, 2024)
Abstract: This research aims to find out how to form discipline and independence in generation-Z, as well as collaborative efforts with parents and society to shape Islamic character in generation-Z. On the other hand, this research also discusses the role of leadership in Islamic education that can contribute to improving the quality of generation-Z, often called the